Trial and error : the autobiography of Chaim Weizmann - Weizmann, Chaim; Horovitz, B. (London : Horovitz Publishing Co., 1950)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: egodocumenten; zionisme; Palestina